ROLE OF HYDROPHILIC SURFACTANTS IN THE EMULSIFICATION MECHANISTICS OF TYPE III SELF-MICRO-EMULSIFYING DRUG DELIVERY SYSTEMS (SMEDDS) - HASAN, NASER M. Y. (International Journal of Applied Pharmaceutics, 2019)
Objective: Evaluation of the self-emulsifying behaviour of type III lipid systems comprising mixed medium chain glycerides (Miglyol 812-Imwitor 988) and wide range of hydrophilic surfactants in an attempt to identify self-emulsifying microemulsion formulations, prevaricate the crystallization tendency of Cremophor RH40 in the pre-microemulsion concentrate, to shed some light on the mechanistic behavior of these systems after aqueous dispersion. Methods: Non-ionic surfactants with HLB in the range 14 to 16.5 are investigated amongst these are; Cremophor RH40, Cremophor EL, Crillet 4 (polysorbate 80), Crillet 1 (polysorbate 20) and Tagat O2. Optimum oil blends of Miglyol 812-Imwitor 988 and various non-ionic surfactant systems were verified using self-emulsification performance studies, oil droplet diameter measurements and dynamic equilibrium phase studies. Results: Oil blends of Miglyol 812 as an oil and Imwitor 988 as a cosurfactant were optimized for microemulsion systems at ratios of 1:1 in the case of Cremophor RH40 or EL, and at 2:3 in the case of Crillet 4 or Tagat O2. In order to obtain small droplet size and fast dispersion rate for type III lipid systems, hydrophilic surfactants with HLB values between 13 and 15 were found to be the optimum. Conclusion: Spontaneous micro-emulsification in type III lipid system was attributed to the “diffusion and stranding” theory. Yet, the formation of liquid crystalline phases as intermediate phases during dilution of the oil formulation with water appears to be quintessential for the mechanistics of emulsification regardless type of lipid class system.